CRISPR-Cas12a powered hybrid nanoparticle for extracellular vesicle aggregation and in-situ microRNA detection - Zhang, Tenghua; Xie, Zihui; Zheng, Xiaohe; Liang, Yuxin; Lu, Yao; Zhong, Hankang; Qian, Feiyang; Zhu, Yuqing; Sun, Ruiting; Sheng, Yan; Hu, Jiaming (Biosensors & bioelectronics, 2024)
Efficient extracellular vesicle (EV) enrichment and timely internal RNA detection for cancer diagnostics are highly desirable and remain a challenge. Here, we report a rapid EV aggregation induced in-situ microRNA detection technology based on cationic lipid-polymer hybrid nanoparticles encapsulating cascade system of catalytic hairpin assembly and CRISPR-Cas12a (CLHN-CCC), allowing for EV enrichment in three-dimensional space and in-situ detection of internal microRNAs in one step within 30 min. The enrichment efficiency (>90%) of CLHN-CCC is demonstrated in artificial EVs, cell-secreted EVs and serum EVs, which is 5-fold higher than that of traditional ultracentrifugation. The sensitive detection of artificial EVs and internal miR-1290 was achieved with the limit of detection of 10 particles/μL and 0.07 amol, respectively. After lyophilization, CLHN-CCC shows no obvious loss of performance within 6 months, making it much more robust and user friendly. This technique could sensitively (sensitivity = 92.9%) and selectively (selectivity = 85.7%) identify low amount miR-1290 in serum EVs, distinguishing early-stage pancreatic cancer patients from healthy subjects, showing high potential for clinical applications.Efficient extracellular vesicle (EV) enrichment and timely internal RNA detection for cancer diagnostics are highly desirable and remain a challenge. Here, we report a rapid EV aggregation induced in-situ microRNA detection technology based on cationic lipid-polymer hybrid nanoparticles encapsulating cascade system of catalytic hairpin assembly and CRISPR-Cas12a (CLHN-CCC), allowing for EV enrichment in three-dimensional space and in-situ detection of internal microRNAs in one step within 30 min. The enrichment efficiency (>90%) of CLHN-CCC is demonstrated in artificial EVs, cell-secreted EVs and serum EVs, which is 5-fold higher than that of traditional ultracentrifugation. The sensitive detection of artificial EVs and internal miR-1290 was achieved with the limit of detection of 10 particles/μL and 0.07 amol, respectively. After lyophilization, CLHN-CCC shows no obvious loss of performance within 6 months, making it much more robust and user friendly. This technique could sensitively (sensitivity = 92.9%) and selectively (selectivity = 85.7%) identify low amount miR-1290 in serum EVs, distinguishing early-stage pancreatic cancer patients from healthy subjects, showing high potential for clinical applications.